Hypothermic preconditioning but not ketamine reduces oxygen and glucose deprivation induced neuronal injury correlated with downregulation of COX-2 expression in mouse hippocampal slices - Shan Jiang; Yong Wu; De-fang Fang; Ying Chen (Elsevier, 2018)
Hypothermic preconditioning is an effective treatment for limiting ischemic injury, but the mechanism is poorly understood. This study was aimed to explore the effect of hypothermic and ketamine preconditioning on oxygen and glucose deprivation (OGD) induced neuronal injury in mouse hippocampal slices, and to investigate its possible mechanism. The population spike (PS) was recorded in the CA1 region of mouse hippocampal slices using extracellular recordings, Na+/K+ ATPase activity in slices was determined by spectrophotometer and the expression of Cyclooxygenase-2 (COX-2) was measured by Western blot. Ten min of OGD induced a poor recovery of PS in slices after reoxygenation. Hypothermic (33 °C) preconditioning delayed the appearance of transient recovery (TR) of PS and improved the recovery amplitude of PS after reoxygenation. Hypothermic preconditioning also decreased the expression of COX-2 and increased Na+/K+ ATPase activity in slices. Pretreatment of ketamine, a non-competitive NMDA receptor antagonist at a subanesthetic dose has no effect on OGD induced neuronal injury. Moreover, the protection of hypothermic preconditioning was not added by ketamine. The downregulation of COX-2 expression and the increase of Na+/K+ ATPase activity may be associated with the effectiveness of hypothermic preconditioning in increasing tolerance to an OGD insult. Keywords: Hypothermic preconditioning, Ketamine, Cyclooxygenase-2, Oxygen and glucose deprivation